JURIDICAL ANALYSIS OF WOMEN AS ABUSERS OF NARCOTICS CLASS I (ONE) TYPE OF SHABU (CASE STUDY OF DECISION NUMBER: 450/PID.SUS/2023/PN.MND) - K.Mahalieng, Abdul; Borman, Syahrul; Prawesthi, Wahyu; Astutik, Sri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This thesis is titled "Legal Analysis of Women as Abusers of Class I Narcotics (Methamphetamine) (Case Study of Ruling Number: 450/PID.SUS/2023/PN.MND)". This research aims to explore the legal aspects related to drug abuse by women in Indonesia, particularly within the framework of criminal law. The case of defendant Angelina Emilia Wowor, involved in the abuse of methamphetamine, serves as the focal point of analysis, including legal practices, criminal liability, and the judges' considerations in imposing sentences. The findings indicate the importance of understanding the social and psychological contexts behind criminal behavior and the need for recommendations for a more humane and just handling in the legal system.